Optic Disk Melanocytoma. The Clinical Case - I. A. Bashkatova; S. O. Shchigareva; E. V. Gromakina; T. V. Yanchenko (Oftalʹmologiâ)
The purpose of the study was to monitor a 6-year-old optic disc melanocytoma.Patient and methods. A clinical case of optic disc melanocytoma revealed in a woman aged 28 when examining the fundus during a second pregnancy. Ophthalmological examination of the patient included clinical and hardware methods: visometry, perimetry, biomicroscopy, binocular and reverse ophthalmoscopy, ultrasound B-scanning, optical coherence tomography of optic disc and retina, fundus photorecording using fundus cameras.Results. A neoplasm of the right eye with clear boundaries is large in size, which is almost completely covers and shields the optic disc, except for a narrow strip of disc in the lower zone, heterogeneous dark brown with a high prominence in the vitreous body of 1.1 mm according to the data of ultrasonic B-scan and 1.15 according to optical coherence tomography. In the layer of nerve fibers, we can note the destruction of the retina adjacent to melanocytoma with single cystic cavities. The retinal ganglion cell complex is normal. The peripheral boundaries of the field of view of the right eye according to perimetry are normal. During the 6-year observation, we can notice 100 % visual acuity and an unchanged field of vision. Signs of slight tumor growth observed in the last year with the advent of choroidal lesion components.Conclusions. The clinical case describes unilateral melanocytoma of the optic disk of large sizes with preservation of 100 % visual acuity for 6 years of observation at low growth rates, which was found during a planned examination of the fundus of the young patient during pregnancy.